The Synthesis of Ba‐ and Fe‐ Substituted CsAlSi2O6 Pollucites. Issue 9 (9th June 2013) - Rodriguez, Mark A.; Garino, Terry J.; Rademacher, David X.; Zhang, Xiaoyi; Nenoff, Tina M.; Vance, L.
<x xml:space="preserve">Abstract</x> Barium‐substituted CsAlSi2O6 pollucites, CsxBa(1−x)/2AlSi2O6, and barium‐ and iron‐substituted pollucites, CsxBa(1−x)/2AlxFe1−xSi2O6 and CsxBa1−xAlxFe1−xSi2O6 were synthesized with 1 ≥ x≥ 0.7 using a hydrothermal synthesis procedure. Rietveld analysis of X‐ray diffraction data confirmed the substitution of Ba for Cs and Fe for Al, respectively. The crystallographic analysis also describes the effects of three different types of pollucite substitutions on the pollucite unit cell: Ba2+ for Cs1+ cation results in little effect on cell dimensions, intermediate concentrations of Ba2+ and Fe3+ substitution result in net minor expansion due to Fe3+ addition, and large Ba and Fe substitutions result in overall framework contraction. Elemental analysis combined with microscopy further supports the phase purity of these new phases. These materials can be used to study the stability of CsAlSi2O6 as a durable ceramic waste form, which could accommodate with time Cs and its decay product, Ba. Furthermore, success in iron substitution for aluminum into the pollucite lattice predicts that redox charge compensation for Cs cation decay is possible.